Synthesis of a Novel Ladder Poly(azomethine-ester) Based on PET Waste Bottles - Issam, A. Mohammed; Shahabuddin, Syed; Kareem, Huda Salah; Mohamad, Sharifah; Saidur, Rahman (Carl Hanser Verlag, 2019)
In the present investigation, a novel ladder polymer, poly(azomethine ester), was prepared via solution polycondensation polymerization between terephthalic acid and the novel monomer. Terephthalic acid was regenerated from PET waste bottles by saponification process, whereas p-phenylenediamine was obtained via Hoffmann rearrangement method. A novel monomer, namely N,N’-bis(2,5-dihydroxy benzylidene)-1,4-diaminobenzene was prepared from the reaction of 2,5-di-hydroxybenzadehyde with p-phenylenediamine in the ratio of 2:1, respectively. For the first time a solution polycondensation method has been employed for the synthesis of a ladder polymer which is otherwise prepared commonly via Diels-Al-der cycloaddition reaction. The synthesized ladder polymer was characterized by Fourier transform infrared spectroscopy (FT-IR), proton nuclear magnetic resonance spectroscopy (1H NMR), carbon nuclear magnetic resonance spectroscopy (13C NMR), elemental analysis (CHN), X-ray diffraction (XRD), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The results revealed that the ladder polymer possess highly regular ladder like framework, and that most of the ester groups have taken part in the side-by-side polymerization reaction. © Carl Hanser Verlag, Munich Intern.